2019
DOI: 10.3390/cancers11122036
|View full text |Cite
|
Sign up to set email alerts
|

Pathways, Processes, and Candidate Drugs Associated with a Hoxa Cluster-Dependency Model of Leukemia

Abstract: High expression of the HOXA cluster correlates with poor clinical outcome in acute myeloid leukemias, particularly those harboring rearrangements of the mixed-lineage-leukemia gene (MLLr). Whilst decreased HOXA expression acts as a readout for candidate experimental therapies, the necessity of the HOXA cluster for leukemia maintenance has not been fully explored. Primary leukemias were generated in hematopoietic stem/progenitor cells from Cre responsive transgenic mice for conditional deletion of the Hoxa locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The HOXA7 gene is a member of the homeobox (HOX) gene family, which plays vital roles in hematopoiesis and cell differentiation ( 25 ). Previous research has shown that the gene HOXA7 is overexpressed in MLL-fusion leukemias, which commonly have very poor outcomes ( 26 29 ). The proteins encoded by S100A10 and S100A11 are members of the S100 family.…”
Section: Discussionmentioning
confidence: 99%
“…The HOXA7 gene is a member of the homeobox (HOX) gene family, which plays vital roles in hematopoiesis and cell differentiation ( 25 ). Previous research has shown that the gene HOXA7 is overexpressed in MLL-fusion leukemias, which commonly have very poor outcomes ( 26 29 ). The proteins encoded by S100A10 and S100A11 are members of the S100 family.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated the efficacy of several drugs targeted towards other diseases (e.g., sodium valproate) in the clinical setting against subtypes of AML [ 9 , 13 ]. More recently, using a combination of connectivity mapping in a conditional model of Mixed-Lineage Leukemia (MLL) AML and drug similarity analysis, we identified FDA-approved candidate drugs (including Salinomycin, Atorvastatin, and Vidofludimus) that potentially target HOXA -dependency in MLL-AF9 leukemia [ 14 ]. For candidate drug studies, the human THP-1 cell line and murine mAF9 primary cells were selected as matched exemplars of AML models that harbor the MLL-AF9 translocation.…”
Section: Introductionmentioning
confidence: 99%